(untitled) - Nakayama, Shigeru (Tokyo, 1984)
This book introduce about two styles of learning, the emergence of paradigms. Paper, printing, and the maturing traditions. Scholarly journals, learned societies, and the rise of moder science...
Keywords: Khoa học,Science; Lịch sử,History; Trung Quốc,China